High neutrophil : lymphocyte ratio is associated with refractory Kawasaki disease. Issue 6 (12th April 2017) - Cho, Hong‐Je; Bak, So Young; Kim, Su Yeong; Yoo, Rita; Baek, Hae‐Sung; Yang, Seung; Hwang, Il‐Tae; Ban, Ji‐Eun
Abstract: Background: The clinical significance of the neutrophil : lymphocyte ratio (NLR) has not yet been fully elucidated in Kawasaki disease (KD). The purpose of this study was to investigate the relationship between NLR and response to i.v. immunoglobulin (IVIG), and its effect on coronary abnormalities in KD. Methods: A total of 196 KD patients treated with IVIG were analyzed. Baseline NLR was evaluated immediately before IVIG therapy and the patients classified into two groups according to NLR. The clinical data, other inflammatory biomarkers, and coronary complications were also assessed. Results: Kawasaki disease patients with NLR ≥ 5 had a greater incidence of IVIG refractoriness than the NLR < 5 group (31.7% vs 4.3%, P < 0.001), but this was not related to the development of coronary abnormalities. The change in NLR after IVIG (i.e. ΔNLR) was significantly decreased in the coronary abnormality group (2.65 ± 1.88 vs 3.81 ± 2.55, P = 0.042). On multivariate analysis, high NLR and CRP were independent predictors of IVIG refractoriness during the acute phase of KD ( P = 0.032 in NLR; P = 0.029 in CRP, respectively). Conclusions: High NLR was closely associated with resistance to IVIG, but it was not related to the occurrence of coronary abnormalities in KD. Low ΔNLR after IVIG, however, was significantly associated with coronary artery abnormalities.